2006
DOI: 10.1128/aem.72.4.2885-2895.2006
|View full text |Cite
|
Sign up to set email alerts
|

Planktonic Replication Is Essential for Biofilm Formation byLegionella pneumophilain a Complex Medium under Static and Dynamic Flow Conditions

Abstract: Legionella pneumophila persists for a long time in aquatic habitats, where the bacteria associate with biofilms and replicate within protozoan predators. While L. pneumophila serves as a paradigm for intracellular growth within protozoa, it is less clear whether the bacteria form or replicate within biofilms in the absence of protozoa. In this study, we analyzed surface adherence of and biofilm formation by L. pneumophila in a rich medium that supported axenic replication. Biofilm formation by the virulent L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
136
0
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 142 publications
(147 citation statements)
references
References 42 publications
2
136
0
9
Order By: Relevance
“…pillar-and mushroom-like structures) formed at 25 u C remained more stably attached than filamentous, mycelial-mat-like biofilms formed at 37 and 42 u C. Also, Mampel et al (2006) reported that biofilm formation at 37 u C was 30 % lower than at 23 and 30 u C. Furthermore, we have shown that adhesion is highest for late stationary phase cells. This is expected, as L. pneumophila shows increased expression of the flagellum and of type IV pili, both of which have been described in other bacteria to be involved in adhesion (O'Toole & Kolter, 1998;Pratt & Kolter, 1998;Watnick & Kolter, 1999), in stationary phase during low-temperature growth (Heuner et al, 1999;Soderberg et al, 2004).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…pillar-and mushroom-like structures) formed at 25 u C remained more stably attached than filamentous, mycelial-mat-like biofilms formed at 37 and 42 u C. Also, Mampel et al (2006) reported that biofilm formation at 37 u C was 30 % lower than at 23 and 30 u C. Furthermore, we have shown that adhesion is highest for late stationary phase cells. This is expected, as L. pneumophila shows increased expression of the flagellum and of type IV pili, both of which have been described in other bacteria to be involved in adhesion (O'Toole & Kolter, 1998;Pratt & Kolter, 1998;Watnick & Kolter, 1999), in stationary phase during low-temperature growth (Heuner et al, 1999;Soderberg et al, 2004).…”
Section: Discussionmentioning
confidence: 65%
“…Although these models do not reflect the complexity found in natural environmental biofilms, monospecies biofilms were the first step towards understanding adaptation to the sessile lifestyle for many bacteria, including two recent studies on L. pneumophila (Mampel et al, 2006;Piao et al, 2006). These models pave the way for the study of complicated microbial interactions and have proven to be useful for assessing the gene expression profile of sessile cells even if the different cell types present within a biofilm cannot be analysed independently by this approach (Schembri et al, 2003;Beloin et al, 2004;Waite et al, 2005;Whiteley et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lpn strains used in this study were JR32 (wt Philadelphia-1) (38), GS3011 (icmT deletion mutant lacking a functional Icm/Dot T4SS; ΔT) (39), thymidine-auxotroph derivatives of Lpn ΔT, and Corby (wt or flaA deletion mutant). Where indicated, Lpn constitutively expressed GFP from plasmid pMMB207-Km14-GFPc (8) or DsRed from plasmid pSW001 (40). Before infections, Lpn was grown for 3 d at 37°C on charcoal yeast-extract agar (CYE) plates.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, at least 20 other species of Legionella have been associated with human infections (16). Legionella bacteria do exist as free-living planktonic forms in the environment (36), intracellular parasites of protozoans (3), and/ or inhabitants of mixed-community biofilms (29).Thus, the diversity of types and the ubiquitous occurrence of legionellae in water environments or moist soil make it difficult to identify epidemic strains, and outbreaks of legionellosis have been associated mainly with contamination of man-made aquatic environments (2,16).…”
Section: Introductionmentioning
confidence: 99%